Locally invasive pulmonary aspergillosis occurring in a gardener: an occupational hazard?. Issue 8 (August 1989) - Zuk, J A; King, D; Zakhour, H D; Delaney, J C
Abstract : Fatal locally invasive pulmonary aspergillosis occurred in a previously fit young patient who had no predisposing factors other than exposure to fungal spores in his occupation as a gardener.